2014
DOI: 10.1111/1467-9477.12040
|View full text |Cite
|
Sign up to set email alerts
|

Changes and Fluctuations in Issue Ownership: The Case of Sweden, 1979–2010

Abstract: Issue ownership (IO) has been an important concept in the analysis of party behaviour, party strategy and party competition for several decades. More recently, it has also been of growing interest for research on voting behaviour. Traditionally, IO has been regarded as a stable phenomenon where parties have different issue profiles and are advantaged by different political issues or issue‐areas. Recently, however, many studies have reported change and fluctuations of IO, and the same studies also makes it clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…While voters' issue ownership perceptions appear relatively stable and persistent on the aggregate level (Seeberg, 2017), albeit not completely resistant to change (e.g., Bélanger, 2003;Christensen et al, 2015), individual voters' issue ownership assessments appear to be highly variable and dynamic (Kleinnijenhuis and Walter, 2014;Lanz and Sciarini, 2016). Although both dimensions of issue ownership have been shown to fluctuate on the individual level in response to campaign information in the media or from parties (e.g., Aalberg and Jenssen, 2007;Dahlberg and Martinsson, 2015;Tresch et al, 2015;Walgrave and Lefevere, 2017;Walgrave et al, 2014;Walgrave et al, 2009;Walgrave and de Swert, 2007), it is often argued that the associative dimension is more stable than competence issue ownership evaluations (e.g., Tresch et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…While voters' issue ownership perceptions appear relatively stable and persistent on the aggregate level (Seeberg, 2017), albeit not completely resistant to change (e.g., Bélanger, 2003;Christensen et al, 2015), individual voters' issue ownership assessments appear to be highly variable and dynamic (Kleinnijenhuis and Walter, 2014;Lanz and Sciarini, 2016). Although both dimensions of issue ownership have been shown to fluctuate on the individual level in response to campaign information in the media or from parties (e.g., Aalberg and Jenssen, 2007;Dahlberg and Martinsson, 2015;Tresch et al, 2015;Walgrave and Lefevere, 2017;Walgrave et al, 2014;Walgrave et al, 2009;Walgrave and de Swert, 2007), it is often argued that the associative dimension is more stable than competence issue ownership evaluations (e.g., Tresch et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…First of all, a considerable amount of over time-variation in issue ownership perceptions has been documented in a number of countries (e.g., Brasher, 2009;Christensen et al, 2015;Goul Andersen and Hansen, 2013;Green and Jennings, 2012;Martinsson, 2009;Meyer and Müller, 2013;Pope and Woon, 2009). Among the causes of this variation, Green and Jennings (2012) find evidence of the impact of events, such as economic shocks, as well as the cost of ruling on what they term 'macrocompetence', a sort of general, non-issue specific 'issue' ownership perception.…”
Section: The (In)stability Of Issue Ownershipmentioning
confidence: 99%
“…For some, probably not least students of party competition, the first solution may seem tempting. Research (e.g., Christensen et al 2015;Stubager and Seeberg 2016;Walgrave et al 2009) has shown, and the tests above confirmed, that issue ownership assessed by the standard measure is a shortterm phenomenon that varies substantially across time. Both the founding fathers and Egan (2013), thus, seem to have been wrong on the temporal dimension.…”
Section: Resultsmentioning
confidence: 66%
“…First, the temporal aspect is not specified leaving respondents to draw on both short-and long-term considerations when answering the question. Although Egan (2013) ends up defining issue ownership as a long-term phenomenon, he (Egan 2013, 53-4) himself points out and recent scholarship (e.g., Christensen et al 2015;Stubager and Seeberg 2016;Walgrave et al 2009) shows that issue ownership assessed using the standard measure can be unstable at both the aggregate and individual levels. This instability is what would be expected based on public opinion theories of priming, agenda-setting (e.g., Iyengar and Kinder 1987;McCombs 2004), and top-of-the-head answering of survey items (cf.…”
Section: Issue Ownership In Action: How Is the Concept Measured?mentioning
confidence: 99%